Nuclear and Nucleolar Alterations in Rat Hepatocytes Following Combined Mycotoxin Exposure (Journal of Innovative Solutions for Eco-Environmental Sustainability, 2025)
Chronic exposure to multiple foodborne mycotoxins poses a significant health risk, yet the nuclear and nucleolar morphological responses of hepatocytes remain insufficiently characterized. This study investigated the cytomorphometric changes in hepatocyte nuclei and nucleoli of rats administered a combination of three common mycotoxins: aflatoxin B1, ochratoxin A, and zearalenone. Experimental animals were divided into three groups receiving daily contaminated feed for 15, 30, or 60 days. Cytological preparations from liver tissues were analyzed using DNA cytophotometry and morphometric methods to quantify nuclear and nucleolar DNA content and area. Results showed that by day 15, the nuclear and nucleolar area and DNA content had significantly increased compared to controls (p
Keywords: mycotoxins; hepatocyteu; nucleolus; cytomorphometry; genotoxicity; ploidy